Compliance with Social Distancing, Face Mask and Sanitizer Use Measures against COVID -19 in Kathmandu Valley - Silwal, Sashi; Dhimal , Meghnath; Bista, Bihungum; Acharya, Astha; Parajuli, Kristina; Pant, Suman; Poudyal, Anil; Ghimire, Ajnish; Gyanwali, Pradip (Journal of Nepal Health Research Council, 2022)
Background: The novel coronavirus has caused significant global impacts and is still continuing. Social distancing, the use of face mask and sanitizer (SMS) measures have become the prominent security measures to diminish the COVID-19 transmission. Hence, this study aims to assess the general public’s compliance towards SMS measures set by the Government of Nepal against COVID-19 in Kathmandu Valley.Methods: This cross-sectional study was conducted in selected public places of Kathmandu valley, Nepal employing an observational checklist from 5-6 August 2020. The practice of using facemask and its types were observed at the individual levels (malls, groceries, shops and 30 vehicles). The practice of SMS was studied in 23 public places that included banks, hospitals, vegetable markets, shopping malls, temples, restaurants and public buses. Results: A total of 23 public places and 4502 individuals were included in the study. More than two-third (72.6%) participants were observed using mask. Among the mask users, 27% did not follow the appropriate technique. Maintaining social distance of 2 meters was less followed by the people in the public places, hospitals and public vehicles. Only 37.5% institutions had set the marking of the social distance of 2 meters. Availability of hand washing facilities with soap or sanitizer was found less in the public places.Conclusions: Overall, the compliance measures of SMS set by the Government of Nepal against COVID-19 were not followed appropriately. Efforts are needed to improve the proper practice of using the mask and conveying the SMS message by the Nepal Government which is important step for the prevention of COVID-19 in Nepal.Keywords: COVID-19; hand washing; social distancing; uses of mask